2022
DOI: 10.1101/2022.09.15.507688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The transcriptional and epigenetic reprogramming associated with chronic IL1β-mediated expansion and myeloid priming in TET2 deficient stem and progenitor cells

Abstract: Clonal hematopoiesis (CH) increases risk for the development of hematological malignancy and cardiovascular disease. IL1β is elevated in patients with CH and its inhibition mitigates cardiovascular risk in murine models with Tet2 loss-of-function. How IL1β alters population dynamics of hematopoietic cells upon Tet2 deletion (Tet2-KO) is not well understood. We demonstrated IL1β expands Tet2-KO neutrophils, monocytes/macrophages, and long-term hematopoietic stem cells with reduced lymphopoiesis. IL1β promoted m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…The most common CHIP mutations occur in genes with epigenetic regulatory function ( Buscarlet et al 2017 ): DNMT3A is a methyltransferase involved in de novo cytosine methylation, and TET2 is a methylcytosine dioxygenase that facilitates demethylation by initiating the conversion of 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC) preferentially in a CpG context ( Zhang et al 2016 ; Buscarlet et al 2017 ; Zink et al 2017 ; Tulstrup et al 2021 ). Cell lineages carrying mutations in DNMT3A or TET2 display atypical responses to inflammation: DNMT3A mutant cells show resilience to inflammatory conditions that are expected to cause normal HSPCs to differentiate and lose their self-renewal capacity ( SanMiguel et al 2022 ), whereas Tet2 mutant cells have shown increased differentiation in the presence proinflammatory cytokines and more rapid myeloproliferation in response to microbial-driven inflammation in mice ( Meisel et al 2018 ; Köhnke and Majeti 2021 ; McClatchy et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The most common CHIP mutations occur in genes with epigenetic regulatory function ( Buscarlet et al 2017 ): DNMT3A is a methyltransferase involved in de novo cytosine methylation, and TET2 is a methylcytosine dioxygenase that facilitates demethylation by initiating the conversion of 5-methylcytosine (5mC) to 5-hydroxymethylcytosine (5hmC) preferentially in a CpG context ( Zhang et al 2016 ; Buscarlet et al 2017 ; Zink et al 2017 ; Tulstrup et al 2021 ). Cell lineages carrying mutations in DNMT3A or TET2 display atypical responses to inflammation: DNMT3A mutant cells show resilience to inflammatory conditions that are expected to cause normal HSPCs to differentiate and lose their self-renewal capacity ( SanMiguel et al 2022 ), whereas Tet2 mutant cells have shown increased differentiation in the presence proinflammatory cytokines and more rapid myeloproliferation in response to microbial-driven inflammation in mice ( Meisel et al 2018 ; Köhnke and Majeti 2021 ; McClatchy et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%